Studying the historical Jesus : a guide to sources and methods - Bock, Darrell L. (Michigan: Grand Rapids : A division of Baker Book House Co., 2002)
Explores the material found in the Gospels to gain a better understanding of the Jesus that walked the earth. Provides both biblical and extra-biblical sources of knowledge about Jesus and traces the history and culture of the life and times of Jesus. Presents a variety of methods for studying the Gospels such as historical and narrative criticisms.
Nonbiblical literary evidence for Jesus -- A basic chronology of Jesus' life -- Political history -- Sociocultural history -- The three quests for the historical Jesus -- Historical criticism -- Source criticism -- Form criticism -- Redaction criticism -- Tradition criticism -- Narrative criticism and Gospel genre.
Includes bibliographical references (pages 217-220) and indexes.
Keywords: Jesus Christ -- Historicity -- Study and teaching; Jesus Christ -- Biography -- Study and teaching; Biographies